Oxytocin neurons in the paraventricular and supraoptic hypothalamic nuclei bidirectionally modulate food intake - Rea, Jessica J.; Liu, Clarissa M.; Hayes, Anna M. R.; Ohan, Rita; Schwartz, Grace M.; Bashaw, Alexander G.; Klug, Molly E.; Decarie-Spain, Lea; Park, Yedam; Kao, Alicia E.; Grinevich, Valéry; Kanoski, Scott E. (Molecular metabolism, 2025)
Objectives - Oxytocin (OT) is a neuropeptide produced in the paraventricular (PVH) and supraoptic (SON) nuclei of the hypothalamus. Either peripheral or central OT administration reduces food intake through reductions in meal size. However, pharmacological approaches do not differentiate whether OT's influence on food intake is mediated by OT neurons located in the PVH vs. the SON. Here we address this gap using both gain- and loss-of-function approaches targeting OT neurons. - Methods - OT neuron-specific designer receptors exclusively activated by designer drugs (DREADDs) were targeted in either the PVH or SON in rats, thus allowing for evaluation of caloric intake following selective activation of OT neurons separately in each nucleus. To examine the physiological role of distinct OT neuron populations in eating behavior, a viral-mediated approach was used to silence synaptic transmission of OT neurons separately in either the PVH or SON. - Results - DREADDs-mediated excitation of PVH OT neurons reduced consumption of standard chow via reductions in meal size. On the contrary, SON OT neuron activation had the opposite effect by increasing standard chow consumption. Consistent with these opposing outcomes, activation of PVH and SON OT neurons simultaneously had minimal effects on food intake. Additional results from chronic loss-of-function experiments reveal that PVH OT neuron silencing significantly increased consumption of a high fat and high sugar diet by increasing meal size whereas SON OT neuron silencing reduced chow consumption by decreasing meal size. - Conclusions - Collectively these findings suggest that PVH and SON OT neurons differentially modulate food intake by either reducing or increasing caloric consumption, respectively.